2021
DOI: 10.1002/ldr.3909
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the sources of soluble organic N (SON) from new litter or indigenous soil in a typical subtropical forest

Abstract: Decomposition of forest litter plays a major role in nitrogen (N) dynamics in soil.However, the effect of new litter on indigenous soil N and its contribution to soil N in natural forest remains unknown. An in situ soil column experiment was conducted and 15 N labelled litter was added to decompose for 14 months to examine the effect of litter retention on soil N dynamics in a typical subtropical forest. Litter removal in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Vegetation restoration has also been found to increase N cycle enzyme activity and reverse soil microbial N limitation in subtropical forest soils [ 14 , 15 ], suggesting that the effects of vegetation restoration can increase soil N turnover and improve the ability to supply N. Yan et al [ 16 ] reported a significant increase in N-cyclase in ecosystem soils during the early stages of restoration, which remained stable as the restoration process progressed. These different results may be due to differences in vegetation cover types, resulting in changes in plant residues, root systems and secretions, and soil properties [ 17 , 18 , 19 ]. Therefore, the effect of vegetation restoration on soil N-cycle enzyme activities in a given environment remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation restoration has also been found to increase N cycle enzyme activity and reverse soil microbial N limitation in subtropical forest soils [ 14 , 15 ], suggesting that the effects of vegetation restoration can increase soil N turnover and improve the ability to supply N. Yan et al [ 16 ] reported a significant increase in N-cyclase in ecosystem soils during the early stages of restoration, which remained stable as the restoration process progressed. These different results may be due to differences in vegetation cover types, resulting in changes in plant residues, root systems and secretions, and soil properties [ 17 , 18 , 19 ]. Therefore, the effect of vegetation restoration on soil N-cycle enzyme activities in a given environment remains unclear.…”
Section: Introductionmentioning
confidence: 99%